2016
DOI: 10.17245/jdapm.2016.16.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Computer-controlled local anesthetic delivery for painless anesthesia: a literature review

Abstract: Local anesthesia is administered to reduce pain during dental treatments, but may itself cause pain and contribute to increased dental fear. Computer-controlled local anesthetic delivery (CCLAD) is one the method to reduce patient pain during local anesthesia; it is a device that slowly administers anesthetics by using a computerized device to control the injection speed. This literature review aims to provide an objective assessment of the usefulness of CCLAD for controlling pain by reviewing papers published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 25 publications
1
59
0
2
Order By: Relevance
“…We are aware that a literature review and a recent systematic review on this subject have been published. Both papers evaluated the use of CCLAD in children and adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that a literature review and a recent systematic review on this subject have been published. Both papers evaluated the use of CCLAD in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, there are divergent results, favouring the use of computerized anaesthesia 3,[5][6][7]13 or showing no difference between the two techniques. 9,[16][17][18][19]22 We are aware that a literature review 23 and a recent systematic review 24 on this subject have been published. Both papers evaluated the use of CCLAD in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, the amount of information is a controversial issue as some patients could experience more anxiety due to an excess of that. Computerized controlled anesthetic delivery systems are able to better control the flow and pressure of the liquid which can reduce pain during local anesthesia infiltration (6,17,19). A recent literature review (19) showed that most studies compared conventional dental anesthesia with computerized controlled anesthesia systems in terms of pain, generally obtaining better results in the maxilla for the computerized one, as measured by visual analogue scales, electric pulp tester, dental anxiety scale, or perceived stress scale.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized controlled anesthetic delivery systems are able to better control the flow and pressure of the liquid which can reduce pain during local anesthesia infiltration (6,17,19). A recent literature review (19) showed that most studies compared conventional dental anesthesia with computerized controlled anesthesia systems in terms of pain, generally obtaining better results in the maxilla for the computerized one, as measured by visual analogue scales, electric pulp tester, dental anxiety scale, or perceived stress scale. Nevertheless, the sound and beeps emitted by The Wand System, the slowness of the anesthetic act and the fact that to observe an unknown anesthetic device could even provoke more fear that a traditional syringe are some unpleasant issues discussed in some studies (10,19).…”
Section: Discussionmentioning
confidence: 99%
“…This aspect could be particularly beneficial for patients suffering from systemic diseases that require peculiar treatment during local anesthesia. The increased comfort and better patient's acceptance during STA have been extensively documented on pediatric dentistry research (11)(12)(13)(14)(15). Several comparative studies between CLA and conventional injections have been conducted also in periodontology, endodontics, prosthetics, maxillofacial surgery and restorative dentistry (15)(16)(17)(18)(19).…”
Section: Effectiveness Of Computer-assisted Anesthetic Delivery Systementioning
confidence: 99%